Developing Students’ Writing Skill by Diary Writing Habit - Fatima A. Putri; Bery Salatar; Susanto SUSANTO (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Writing is a process of expressing feelings, thoughts, and ideas in the form of graphic language and it is one of English skills that should be mastered by the English language learners (Harmer, 2004; Meyers, 2005). To develop and improve students’ writing skill,  diary can be used as one of teaching media (Ningrum, Rita & Hastini, 2013). The paper presents a pleliminary study on developing the writing skill of the students by diary writing habit. The participants in the research are the 4th semester students, Teacher Training and Education Faculty, English Education Program, Bandar Lampung University. It is found that the habit is useful to develop the students’ writing skill.